Strain‐Controlled Spin Wave Excitation and Gilbert Damping in Flexible Co2FeSi Films Activated by Femtosecond Laser Pulse. (15th January 2021) - Zhang, Zhi; Liu, Er; Lu, Xianyang; Zhang, Wen; You, Yurong; Xu, Guizhou; Xu, Zhan; Wong, Ping Kwan Johnny; Wang, Yichuan; Liu, Bo; Yu, Xiaojiang; Wu, Jing; et al.
Abstract: The dynamic response of magnetic order to optical excitation at sub‐picosecond scale has offered an intriguing alternative for magnetism manipulation. Such ultrafast optical manipulation of magnetism has become a fundamental challenging topic with high implications for future spintronics. Here, this study demonstrates such manipulation in Co2 FeSi films grown on flexible polyimide substrate, and demonstrates how the magneto‐optical interaction can be modified by using strain engineering which in turn triggers the excitation of both dipolar and exchange spin waves modes. Furthermore, Gilbert damping and spin‐orbit coupling in Co2 FeSi can both be tuned significantly by altering the magnitude and type of applied strain, suggesting an appealing way to manipulate spin wave propagation. These results develop the optical manipulation magnetism into the field of spin wave dynamics, and open a new direction in the application of spin orbitronics and magnonics devices using strain engineering. Abstract : An ultrafast optical technique is developed into the field of magnonics and how the magneto‐optical interaction in Co2 FeSi films can be modified using strain engineering with the flexible substrate, which in turn can control the spin waves excitation and Gilbert damping in Co2 FeSi is demonstrated, suggesting a new direction for the design of magnonic switch or logic devices.